2011
DOI: 10.1063/1.3601763
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion relation for pure dust Bernstein waves in a non-Maxwellian magnetized dusty plasma

Abstract: Pure dust Bernstein waves are investigated using non-Maxwellian kappa and (r,q) distribution functions in a collisionless, uniform magnetized dusty plasma. Dispersion relations for both the distributions are derived by considering waves whose frequency is of the order of dust cyclotron frequency, and dispersion curves are plotted. It is observed that the propagation band for dust Bernstein waves is rather narrow as compared with that of the electron Bernstein waves. However, the band width increases for higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…For r = 0 and q ⟶ ∞ , we found that our results agree with those obtained by Duan [11]. Moreover, we recognize that the present work could be useful in interpreting and understanding many phenomena taking place in different regions in the Saturn's moon Titan [38,39] and other space regions, such as ionosphere, solar wind, cometary tails [40,41] which have dust grains obeying non-maxwellian distributio.…”
Section: Discussionsupporting
confidence: 85%
“…For r = 0 and q ⟶ ∞ , we found that our results agree with those obtained by Duan [11]. Moreover, we recognize that the present work could be useful in interpreting and understanding many phenomena taking place in different regions in the Saturn's moon Titan [38,39] and other space regions, such as ionosphere, solar wind, cometary tails [40,41] which have dust grains obeying non-maxwellian distributio.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, our numerical investigations should be of wide relevance to explain and interpret various regions in the Saturn's moon Titan [54,55] and other space regions, such as ionosphere, solar wind, cometary tails [56,57] where the particles follow a non-Maxwellian distribution. Moreover, these findings may be helpful to understand the basic features of the nonlinear structures of the DAWs propagating in such space regions and to control (minimize) the dissipated energy in these regions.…”
Section: Numerical Results and Conclusionmentioning
confidence: 99%
“…Later authors also observed that the propagation band for dust Bernstein waves is rather narrow as compared with that of the electron Bernstein waves. However, the band width increases for higher harmonics, for both kappa and (r,q) distributions [22].…”
Section: Introductionmentioning
confidence: 95%
“…By starting with Kinetic Vlasov-Boltzmann Equation in perturbed linearized distribution function (21) and substituting the Generalized (r,q) distribution function is of the form (22) r and q are the spectral indices where r represents the shoulder profile and q is for high energy tail. Now applying plane wave solution and solving for fji and introducing the density perturbation equation…”
Section: Dispersion and Growth Of Dust Acoustic Waves In Non-maxwelli...mentioning
confidence: 99%